Differential FeS cluster photodamage plays a critical role in regulating excess electron flow through photosystem I - Tiwari, Arjun; Mamedov, Fikret; Fitzpatrick, Duncan; Gunell, Sanna; Tikkanen, Mikko; Aro, Eva-Mari (Springer Nature, 2025)
The photosynthetic electron flux from photosystem I (PSI) is mainly directed to NADP+ and CO2 fixation, but a fraction is always shared between alternative and cyclic electron transport. Although the electron transfer from P700 to ferredoxin, via phylloquinone and the FeSX, FeSB and FeSA clusters, is well characterized, the regulatory role of these redox intermediates in the delivery of electrons from PSI to NADP+, alternative and cyclic electron transport under environmental stress remains elusive. Here we provide evidence for sequential damage to PSI FeS clusters under high light and subsequent slow recovery under low light in Arabidopsis thaliana. Wild-type plants showed 10-35% photodamage to their FeSA/B clusters with increasing high-light duration, without much effect on P700 oxidation capacity, FeSX function or CO2 fixation rate, and without additional oxygen consumption (O2 photoreduction). Parallel FeSA/B cluster damage in the pgr5 mutant was more pronounced at 50-85%, probably due to weak photosynthetic control and low non-photochemical quenching. Such severe electron pressure on PSI was also shown to damage the FeSX clusters, with a concomitant decrease in P700 oxidation capacity and a decrease in thylakoid-bound ferredoxin in the pgr5 mutant. The results from wild-type and pgr5 plants reveal controlled damage of PSI FeS clusters under high light. In wild-type plants, this favours electron transport to linear over alternative pathways by intact PSI centres, thereby preventing reactive oxygen species production and probably promoting harmless charge recombination between P700+ and FeSX- as long as the majority of FeSA/B clusters remain functional.